The Determinants of Drug-Resistant Tuberculosis Incidence at the Special Lung Hospital, Health Department of the Provincial Government of North Sumatera, 2021-2024 - Dalimunthe, Mawaddah Sri Rezeki; Susanti, Nofi; Aidha, Zuhrina; Batubara, Abdul Karim (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Along with the increase in tuberculosis (TB) cases, there has also been a rise in the number of Drug-Resistant Tuberculosis (DR-TB) cases, which poses a serious threat to global TB control efforts. Globally, there are 400,000 DR-TB cases according to the WHO report in 2024, with Indonesia contributing 7.4% of the total cases. In North Sumatra, the incidence of DR-TB cases reached 54%. This study aims to analyze and identify the factors influencing the incidence of DR-TB among DR-TB patients at the Special Lung Hospital of the Provincial Government of North Sumatra. The study uses a quantitative approach with a case-control design utilizing secondary data from the SITB application at the Special Lung Hospital of the Provincial Government of North Sumatra from 2021-2024. The sample consists of 204 individuals with a 1:1 ratio, comprising 102 individuals with DR-TB and 102 controls with non-DR-TB. The sampling technique used is purposive sampling. This study sets DR-TB incidence as the dependent variable, while independent variables include sex, employment status, age, treatment outcome, access to health service facilities, residence, contact examination, TB treatment history, diagnosis type, diabetes mellitus status, and HIV status. Data were analyzed using three tests: univariate analysis, bivariate analysis, and multivariate analysis with the use of statistical software version 22. The results show that factors significantly influencing DR-TB incidence include age (CI 95%: 4.7 [2.3-9.5]), employment (CI 95%: 3.4 [1.7-6.6]), and a history of previous TB treatment (CI 95%: 14.7 [5.5-39]).